Electrically tunable large magnetoresistance in graphene/silicon Schottky junctions. (October 2017) - Wang, Xiaojuan; Wang, Tao; Yang, Dezheng; Yang, Zhaolong; Li, Dong; Chen, Mingyuan; Si, Mingsu; Xue, Desheng; Zhang, Zengxing
Abstract: It should be a promising paradigm for graphene application in semiconductor industry by incorporating graphene into silicon to improve the behavior of silicon-based devices or develop high-performance devices with a new physical mechanism. Here we report on a large positive magnetoresistance (MR) over 80% at a magnetic field of 2.2 T and a temperature of 80 K in graphene/Si Schottky junctions by stacking chemical vapor deposition derived monolayer graphene on silicon. The produced MR is anisotropic and dependent on the angle between the direction of the magnetic field and the configuration plane, and can be modulated by the electrical bias across the configuration due to the built-in electric field. The MR effect should be ascribed to the charge carriers scattering and the released silicon magnetic moments in the graphene/Si interface that is suggested by first principles calculations. The study here should be helpful to understand the interface between the graphene and silicon, develop high-performance silicon based devices, complement the extraordinary properties of graphene and open one possible way to exploit their application for magneto-electronics. Graphical abstract: